ASSISTANCE OF REGISTRATION OF TEH TARIK SULTAN POENYA ANASIS TRADEMARK AS INTELLECTUAL PROPERTY IN BATAM CITY - Fientery Fientery; Hari Sutra Disemadi (ConCEPt - Conference on Community Engagement Project, 2022)
A brand is a sign that is displayed graphically in the form of images, logos, letters, words, and color arrangements in the form of 2 or 3 dimensions by combining 2 or 3 of these elements which creates a difference in goods and or services produced by people or legal entities in trading activities. The brand itself is also included in the type of Intellectual Property that we often encounter in our daily lives. However, although brands are often found in our daily lives, most of these brands are still not registered with the DJKI, one of which is the brand “Teh Tarik Sultan Poenya Anasis”. The reason the owner of the “Teh Tarik Sultan Poenya Anasis” brand has not been registered by the owner to the DJKI is because the owner of the mark still does not understand the procedure for registering the mark online on the DJKI website. Therefore, it is necessary to provide assistance to the registration of the mark. The method of implementing community service is carried out in 3 stages, namely, firstly determining the problems owned by partners, secondly preparing for the resolution of partner problems and the last is implementation. The result of the implementation of this community service is the understanding of partners in the stages and procedures in registering a mark in the DJKI and that the mark has been registered with the DJKI.